2022
DOI: 10.1177/09544100221106656
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective nozzle design optimization for maximum thrust vectoring performance

Abstract: Thrust vectoring is a promising technology that offers the potential for improved maneuverability, control efficiency, and stealth characteristics of aircraft. Optimized nozzle design over a range of operating conditions is one of the most crucial factors for maximum thrust vectoring operation. Our goal was to investigate the optimal design of bypass dual throat nozzle to maximize thrust vectoring. We performed a multi-objective optimization study by varying the nozzle bypass angle, convergence angle, and bypa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Optimization of the bypass dual throat nozzle has been carried out by analyzing three aspects of the nozzle parameters. It was found that bypass angle and bypass width have a significant impact on the thrust vectoring performance of the nozzle [126].…”
Section: Effect Of Nprmentioning
confidence: 99%
“…Optimization of the bypass dual throat nozzle has been carried out by analyzing three aspects of the nozzle parameters. It was found that bypass angle and bypass width have a significant impact on the thrust vectoring performance of the nozzle [126].…”
Section: Effect Of Nprmentioning
confidence: 99%
“…The performance parameters considered are thrust, discharge coefficients, vectoring angle and efficiency. Thrust vectoring parameter is calculated as [49],…”
Section: Ftv Performance Parameters Consideredmentioning
confidence: 99%
“…Firstly, the internal flow field is calculated by using numerical simulations, and the experimental values are verified. Then, the performance of the swirling–straight composite nozzle is compared with those of the pressure swirl nozzle and the straight jet nozzle 18,19 . Finally, the influence of the straight jet aperture on the performance is analyzed, which provides guidance for the design optimization of the swirling–straight composite nozzle 20 …”
Section: Introductionmentioning
confidence: 99%